Thoracoscopic Repair of Oesophageal Atresia: Results of a Selective Approach - Dingemann, Carmen; Zoeller, Christoph; Ure, Benno (European Journal of Pediatric Surgery, 2013)
Introduction The repair of oesophageal atresia (OA) and tracheoesophageal fistula (TOF) may be routinely performed via thoracoscopy. However, data on the feasibility and efficacy of thoracoscopic OA/TOF repair are scarce and some authors reported a high rate of anastomotic leak. The aim of this study was to evaluate our concept of OA/TOF repair which includes specific selection of patients and a selective surgical approach.Patients and Methods The study was approved by the Institutional Review Board and written informed consent was obtained from all guardians for anonymized data analysis. All patients undergoing OA/TOF repair from June 2001 to December 2011 were included in this analysis. Thoracoscopy was used in cardiorespiratory stable newborns with OA/TOF and a birthweight of ≥ 2000 g. In case of any intraoperative adverse events, lack of progress for ∼15 minutes, or anastomosis under tension, the procedure was converted to open thoracotomy. Study endpoints were conversion rate and postoperative complications.Results A total of 44 newborns with OA/TOF were operated, of whom 22 (6 females, 16 males) met our criteria for a thoracoscopic approach. The mean birthweight of thoracoscopically operated patients was 2760 (2020 to 3960) g, 7 were < 36 weeks of gestation. The mean operative time was 142 (75 to 220) minutes. Thoracoscopy was converted to thoracotomy in eight patients due to problems with exposition (n = 2), ventilation (n = 3), anastomosis under tension (n = 2), or bleeding (n = 1, no transfusion). There was no anastomotic leak in the group of patients who underwent successful thoracoscopic repair, but one recurrence of TOF. Two anastomotic leaks emerged in patients in whom the operation was converted. A total of 7 out of the 22 children required endoscopic dilatation. There was no mortality during a mean follow-up of 5.5 years (43 days to 10.6 years).Conclusion Our approach included meticulous patient selection and prompt conversion in case of any adverse events. With this approach, thoracoscopic repair of OA/TOF can be safely performed achieving excellent results and a low rate of complications.
Keywords: oesophageal atresia; tracheoesophageal fistula; thoracoscopy; neonate; outcome